NON-MARKOVIAN ENTANGLEMENT DYNAMICS OF OPEN QUBIT SYSTEM FOR CAVITY QUANTUM ELECTRODYNAMICS AND QUADRATIC SPIN-BOSON MODEL - Aryo Wasesatama, Vincentius
All realistic quantum systems will interact with their environments. This physical fact presents challenges to the implementation of quantum systems for practical and macroscopic systems. One of the most important quantum resources is the implementation of entanglement. In this works, we investigate the interplay between the effects of noisy environments and the dynamics of entanglement. In the first part, the current proposal and theory that best describes an open quantum system and quantification of entanglement are presented. The open quantum systems that will be considered are cavity quantum electrodynamics (CQED) and spin-boson with some modification of both models. Quantum state dynamics for CQED models is obtained exactly and for quadratically coupled spin-boson, using Feynman path integral formulation and hierarchical equation of motion (HEOM) method, obtained numerically. From the dynamical solution of each model, the value of entanglement is measured using Wotters concurrence and its lower bound method, ????????????????, proposed by Li et.al. By adjusting the environmental parameters, we obtained dynamics of the quantum state and entanglement for various degrees of non-markovianity. We also found revivals, dark periods, and elongated times of entanglement that depend on the value of non-markovianity degree. For each model in this study, non-Markovian effect of the environment can better preserve the entanglement of quantum systems.